ANALISIS PEMAKAIAN FUEL IONIZER TERHADAP UNJUK KERJA DAN GAS BUANG PADA MOTOR BENSIN - -, Sudarsono (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2005)
The research will compare gasoline engine by using fuel ionizer device with stan-dard condition focusing on engine performance and exhausted emission. From the ana-lysis it can be proved that by using Fuel ionizer , the maximum torque obtained was in re-volution 6000 rpm with 9,7 Nm. There is an increase about 2,06 % from standard con-dition with 9,5 Nm. The power that was produced in high revolution 6000 rpm also increa-sed 2,05 % with the use of Fuel Ionizer. The minimum power increased 2,7% in revolution 1500 rpm .The use of Fuel Ionizer caused Bmep increased 7,67 %, SCF decreased 17,55 % and efficiency increased 16,32 %. For exhausted emission, the use of fuel ioni-zer caused CO decreased 1,8% - 13,10%. HC decreased 1,3% -19,7%, CO2 increased 8% - 13,7%, while O2 has various values; in revolution 2500 rpm – 3000 rpm there was an increase in CO content and in revolution 3500 rpm-6000 rpm, the content of O2 in standard condition was higher and Lambda value increased 0,13% - 2,62% after using Fuel Ionizer.